2021
DOI: 10.4236/ojpsych.2021.112008
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use Pattern among Nursing Students in Jos, North Central Nigeria

Abstract: Aim: To establish the substance use pattern and psychological distress among the in-coming nursing students of the College with a view towards recommending ways to prevent or reduce complications of substance use disorder in the college. Study design: A cross-sectional design was used. Place and duration: The study took place at the College of Nursing and Midwifery, Jos, Plateau state between the 3 rd and 14 th of February, 2020. Methodology: The study was carried out during the orientation program of the 206 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Research had shown that the patterns of use, episodic and frequent psychoactive substance were found strongly associated with lower socioeconomic status and lower parental education [23]. Epidemiological survey conducted in Jos South, North Central Nigeria by Charles [24] put the proportion of alcohol use at 93.8%, cough syrup (67.0%), tramadol (65.0%), cigarette (35.6%) and cannabis (26.8%). Study had demonstrated that about 6% of the respondents had used cannabis once or twice, and daily (1.5%), while 2.3% of the respondent had used ecstasy once or two times, while 0.5% daily in the last 30days [25].…”
Section: Introductionmentioning
confidence: 99%
“…Research had shown that the patterns of use, episodic and frequent psychoactive substance were found strongly associated with lower socioeconomic status and lower parental education [23]. Epidemiological survey conducted in Jos South, North Central Nigeria by Charles [24] put the proportion of alcohol use at 93.8%, cough syrup (67.0%), tramadol (65.0%), cigarette (35.6%) and cannabis (26.8%). Study had demonstrated that about 6% of the respondents had used cannabis once or twice, and daily (1.5%), while 2.3% of the respondent had used ecstasy once or two times, while 0.5% daily in the last 30days [25].…”
Section: Introductionmentioning
confidence: 99%